Towards the Internet of Things : architectures, security, and applications /: architectures, security, and applications. ([2020]) - Jamali, Mohammad Ali Jabraeil; Bahrami, Bahareh; Heidari, Arash; Allahverdizadeh, Parisa; Norouzi, Farhad
No abstract available